(untitled) - Scott, Allan W. (Hoboken, N.J., 2005)
Understanding Microwaves covers all the important microwave terminology, devices, and systems, and provides an understanding of how everything fits together to make communications, navigation, and radar equipment. The text is geared toward engineers new to the microwave industry, as well as technicians, managers, and students. This field-tested book presents material the author has used in industrial training courses for thousands of students. It is easy to understand and avoids complex mathematics. With extensive exercises at the end of each chapter, and answers at the end of the book, it is suitable for self-study or as a text for industrial seminars and college courses. First, the coverage details the special language of microwaves. Then, it outlines all of the unique devices that are used in microwave equipment and explains how these types fit together to make a typical microwave system, describing what they do, how they work, and what their important performance characteristics are. Finally, the book covers all of the important types of microwave systems, including their structure, function, and applications. Understanding Microwaves is a complete introduction to this important field.
Keywords: Microwave devices